Exploring the role of standards-based descriptors in promoting translation learners’ metacognitive strategy use and translation performance - Mei, Huan; Chen, Yingying (Frontiers in Psychology, 2025)
This study explores the role of China’s Standards of English Language Ability (CSE) descriptors as metacognitive support in promoting translation learners’ metacognitive strategy use and translation performance. Forty students from two parallel classes participated, with the experimental group (n = 20) provided with CSE metacognitive descriptors during the translation course while the control group (n = 20) was not. Adopting a pretest-posttest design, qualitative analysis of students’ translation processes and products were conducted to investigate students’ use of metacognitive strategies. Quantitative assessment of students’ translation output was conducted to investigate their translation performance. Moreover, qualitative data from journal entries were analyzed to explore students’ perceptions of the metacognitive support. Results showed that CSE descriptors had an observable impact on translation learners’ metacognitive strategy use. However, the presence of metacognitive support did not significantly affect students’ overall translation performance. The study concludes that standards-based descriptors can be useful pedagogical tools for metacognitive translator training.